Fast and Minimal‐Solvent Production of Superinsulating Silica Aerogel Granulate. (23rd March 2017) - Huber, Lukas; Zhao, Shanyu; Malfait, Wim J.; Vares, Sirje; Koebel, Matthias M.
Abstract: With their low thermal conductivity ( λ ), silica aerogels can reduce carbon emissions from heating and cooling demands, but their widespread adoption is limited by the high production cost. A one‐pot synthesis for silica aerogel granulate is presented that drastically reduces solvent use, production time, and global warming potential. The inclusion of the hydrophobization agent prior to gelation with a post‐gelation activation step, enables a complete production cycle of less than four hours at the lab scale for a solvent use close to the theoretical minimum, and limits the global warming potential. Importantly, the one‐pot aerogel granulate retains the exceptional properties associated with silica aerogel, mostly λ =14.4±1.0 mW m −1 ⋅K −1 for the pilot scale materials, about half that of standing air (26 mW m −1 ⋅K −1 ). The resource‐, time‐, and cost‐effective production will allow silica aerogels to break out of its niche into the mainstream building and industrial insulation markets.